The Effectiveness of Early Childhood Inclusive Education Textbook for Students of Inclusive Education Classes in UNIMED - Suri Handayani; Nurmaniah Nurmaniah; Srinahyanti Srinahyanti; Santa Situmorang (BIRCU, 2020)
The purpose of this research is to describe effectiveness of early childhood inclusive education textbook for students of inclusive education classes in Unimed. The development of this textbook is a type of research and development (R&D) with the Four-D (4-D) model. This model consists of 4 stages of development, namely Define, Design, Develop, and Disseminate. The sample for this research was students of inclusive education classes in teacher education of early childhood education FIP Unimed, uses purposive sampling technique. The instrument used was an effectiveness sheet filled in by students of inclusive education classes. Data analysis technique is a descriptive analysis in the form of a percentage, while the development of textbook is done through content analysis. Based on the results of student trial, the developed textbook is categorized as very effective with a value of 76.